Synchronous electrochemical evolution of electrode and performance enhancement of sodium ion battery anode - Chao Shen; Heng-Guang Zhang; Gan-Qiang Song; Lu Huang; Dong Wang; Ying-Peng Wu (Cell Reports Physical Science, 2021)
Summary: Irreversible structure evolution of electrode in the battery always leads to structure collapse and the lost activation of active material. To overcome this technical challenge, synchronous electrochemical reconstruction method is proposed. Herein, as a proof of concept, Bi2Se3 nanosheets are synthesized. It shows an outstanding electrochemical performance as the anode of sodium-ion battery, which is benefitted by structure evolution of Bi2Se3 electrode. More importantly, Cu element deriving from the current collector is detected, which plays a crucial role in this evolution, promoting the electrochemical reconstruction and stabilizing selenium element. The role of Cu is further verified by the Se powder anode. The reconstructed anode from Bi2Se3 nanosheet or pure selenium can not only provide a stable structure but also ensure a faster electronic and ionic diffusion channel, leading to an excellent cyclic and rate performance. Therefore, the reconstruction strategy will be a promising way for the design of electrode with high performance.